EFL thesis writing anxiety: Causes, effects, and coping strategies - Atin Kurniawati; Arief Eko Priyo Atmojo (Universitas Merdeka Malang, 2022)
This present study explores how thesis writing anxiety causes delay in thesis writing completion along with its coping strategies. It adopted narrative inquiry as the research method. The participant was one former student of English education graduate program at a state university in Central Java, Indonesia. Data were garnered through semi-structured interviews. The data were then analyzed by employing thematic analysis. The results suggest that thesis writing anxiety was caused by family and financial problems, full-time working duties and poor time management, as well as unpleasant administrative staff services. Thesis writing anxiety empirically affected thesis writing completion in terms of thesis writing procrastination as well as lack of confidence and feeling worried of making mistakes. Successful coping strategies include identifying problems and seeking solutions, establishing mutual communication with thesis supervisors and workplace stakeholders, as well as maintaining self-motivation. Practical implications and suggestions for further studies are also discussed.DOI: 10.26905/enjourme.v7i2.8004